1998
DOI: 10.1017/s000748530002592x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory responses of Glossina fuscipes fuscipes (Diptera: Glossinidae) to the monitor lizard Varanus niloticus niloticus

Abstract: Visual and olfactory responses of Glossina fuscipes fuscipes Newstead to the monitor lizard, Varanus niloticus niloticus Laurenti were studied using various catching devices near Lake Victoria, Kenya. Electric nets baited with visible lizards caught more males (x2.1) and significantly more females (x2.0) than unbaited nets. Lizards concealed in electrified black PVC pipe models, simulating the shape and size of a monitor lizard, increased significantly the catches of tsetse by 2.1 times. Fresh lizard urine dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…seem unresponsive to mammalian odours, the present results show that there is a clear and consistent response to natural lizard odour, according with the findings of Gouteux [19] and Mohamed-Ahmed [18] . However, in the present study, lizard urine had no significant effect whereas Mohamed-Ahmed [18] found that urine doubled the catch of female G. f. fuscipes attracted to an electrocuting cylinder and increased the catch of tsetse from a trap 1.5×. However even his results are marginal: the increase with the electrocuting cylinder are not significant for either males or females analysed separately, and the increase with traps is only significant for males.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…seem unresponsive to mammalian odours, the present results show that there is a clear and consistent response to natural lizard odour, according with the findings of Gouteux [19] and Mohamed-Ahmed [18] . However, in the present study, lizard urine had no significant effect whereas Mohamed-Ahmed [18] found that urine doubled the catch of female G. f. fuscipes attracted to an electrocuting cylinder and increased the catch of tsetse from a trap 1.5×. However even his results are marginal: the increase with the electrocuting cylinder are not significant for either males or females analysed separately, and the increase with traps is only significant for males.…”
Section: Discussionsupporting
confidence: 91%
“…In the course of conducting the experiments in Kenya, we frequently observed tsetse resting on the ground near the host for extended periods; behaviour that we have not seen during our studies of Morsitans tsetse. Other studies have reported that lizard urine is effective [18] – might the residues of lizards cause tsetse to congregate in areas where lizards are common, such as basking points along the lake shore?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, while odor attractants released at large targets have proved much less effective for riverine tsetse than for savannah species, it could be expected that odors might be more useful with smaller targets. For example, lizard odor doubled the numbers of G. f. fuscipes landing on a small tube (as well as a larger target) [27] , [28] . Presumably, the distinctively strong response of G. f. fuscipes to tiny targets relates to this species feeding often on lizards [16] rather than on the large, active, and relatively scarce herbivores that dominate the diet of savannah tsetse [29] .…”
Section: Discussionmentioning
confidence: 99%